(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
Between 2019 and 2024, the Center for Institutional Innovation Studies at the National University of Cuyo (CEII – UNCUYO – CONICET) developed a project on child and adolescent labor in the agricultural sector of Mendoza, within the framework of the ILO’s Offside Project. The project emphasized equal opportunities for women in the world of work, and specifically addressed the situation of girls, adolescents, and women. To this end, an intervention strategy was designed with broad territorial coverage in rural departments of the province, with actions targeting different groups. This article presents the main findings of this work process. It also examines lessons learned from the experience of dialogue between the university, the community, and territorial institutions with the aim of denaturalizing conditions of inequalities and generating tools to improve the situation of children and adolescents in rural areas.